Self-commissioning of interior permanent- magnet synchronous motor drives with high-frequency current injection - Odhano, S; Giangrande, Paolo; Bojoi, R.I.; Gerada, C. (IEEE, 2014)
In this paper, a simple and robust method for parameter estimation at rotor standstill is presented for interior permanent magnet (IPM) synchronous machines. The estimated parameters are the stator resistance through dc test, the dq inductances using high-frequency injection, and the permanent magnet flux by means of a closed-loop speed control maintaining rotor stationary. The proposed method does not require either locking the rotor or additional/special power supplies. The validity of the suggested method has been verified by implementation on two IPM motor prototypes. Finally, the estimated parameters have been compared against results obtained through finite-element simulations and with machine magnetic characterization, separately performed, to validate the method's effectiveness. Saturation and cross-saturation effects are taken care of through amplitude modulation and cross-axis current application, respectively.